Euro area labour markets: different reaction to shocks? - Jan Brůha; Beatrice Pierluigi; Roberta Serafini (European Central Bank (ECB), 2011)
A small labour market model for the six largest euro area countries (Germany, France, Italy, Spain, the Netherlands, Belgium) is estimated in a state -space framework. The model entails, in the long run, four driving forces: a trend labour force component, a trend labour productivity component, a long-run inflation rate and a trend hours worked component. The short run dynamics is governed by a VAR model including six shocks. The state-space framework is convenient for the decomposition of endogenous variables in trends and cycles, for shock decomposition, for incorporating external judgement, and for running conditional projections. The forecast performance of the model is rather satisfactory. The model is used to carry out a policy experiment with the objective of investigating whether euro area countries differ in the labour market adjustment to a reduction in labour costs. Results suggest that, following the 2008-09 recession, moderate wage growth would significantly help delivering a more job-intense recovery.
Keywords: C51; C53; E17; J21; 330; forecasting; Kalman filter; Labor market